2009
DOI: 10.1210/en.2008-0456
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Trophoblast Invasion-Related Genes: Heme Oxygenase-1 Controls Motility via Peroxisome Proliferator-Activated Receptor γ

Abstract: Invasion of cytotrophoblasts (CTBs) into uterine tissues is essential for placental development. To identify molecules regulating trophoblast invasion, mRNA signatures of purified villous (CTB, poor invasiveness) and extravillous trophoblasts (EVTs) (high invasiveness) isolated from first trimester human placentae and villous explant cultures, respectively, were compared using GeneChip analyses yielding 991 invasion/migration-related transcripts. Several genes involved in physiological and pathological cell in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 53 publications
8
91
0
2
Order By: Relevance
“…Recently it has been shown that HO-1 can induce PPAR transcription activity (Bilban et al, 2009). In the present study we used two different methods; PPARa-siRNA in vitro and PPARa knockout mice in vivo, to confirm that the induction of HO-1 expression in the renal tubular cells is dependent on PPARa (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Recently it has been shown that HO-1 can induce PPAR transcription activity (Bilban et al, 2009). In the present study we used two different methods; PPARa-siRNA in vitro and PPARa knockout mice in vivo, to confirm that the induction of HO-1 expression in the renal tubular cells is dependent on PPARa (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…49 In normal placentae, ZO-1 and occludin are localized to the syncytium and villous trophoblast, but are not expressed in EVT. 76 The present literature as well as published mRNA expression data, 77 which are available at GEO profiles (accession number GDS3523[ACCN]), also suggests that many features of EMT such as downregulation of junction proteins (CLDN1/4, OCLN, MPP5, ZO1), and upregulation of EMT-associated and -promoting genes (ITGA5, ITGB1, FSP1, SPARC, HSP47, SNAIL, TCF-4, FN1) occur during EVT differentiation of cytotrophoblasts (CTB) (Fig. 2).…”
Section: Downstream Gene Targets/cell-adhesion Molecules In Emtmentioning
confidence: 85%
“…In contrast to two recent studies (26,36), the VT and EVT preparations were highly purified and used directly after isolation without in vitro culture to minimize transcriptional changes that may occur with cell culture. Interestingly, the signature for TACSTD2+ VT (27) did not match the transcriptional signature for EGFR1+ VT and may indicate that these are distinct subtypes of VT.…”
Section: Discussionmentioning
confidence: 99%